2023
DOI: 10.3389/fnmol.2023.1141079
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease pathogenetic progression is associated with changes in regulated retained introns and editing of circular RNAs

Abstract: IntroductionThe molecular changes leading to Alzheimer’s disease (AD) progression are poorly understood. A decisive factor in the disease occurs when neurofibrillary tangles (NFT) composed of microtubule associated protein tau (MAPT) form in the entorhinal cortex and then spread throughout the brain.MethodsWe therefore determined mRNA and circular RNA changes during AD progression, comparing Braak NFT stages I-VI. Total RNA was isolated from human brain (entorhinal and frontotemporal cortex). Poly(A)+ RNA was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…We previously reported that circular RNAs are translated after undergoing adenosine to inosine RNA editing, caused by ADAR1 or ADAR2 [12,29]. There are two major isoforms of ADAR1: ADAR1-p150 and ADAR1-p110.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that circular RNAs are translated after undergoing adenosine to inosine RNA editing, caused by ADAR1 or ADAR2 [12,29]. There are two major isoforms of ADAR1: ADAR1-p150 and ADAR1-p110.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, this pattern of dysregulation is not mirrored in the linear counterparts of these circRNAs, which exhibit no significantly differential expression between AD and control samples (Fig) (Rybak-Wolf A et al 2015 ). A study using poly(A) + RNA samples obtained from AD brains also displayed no correlation in expression levels between the most abundant circRNAs and their mRNA counterparts through ranking (Arizaca Maquera KA et al 2023 ). The heightened expression of dysregulated circRNAs could potentially serve as indicative markers of their involvement in AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the challenges posed by the short reads and 3′ bias in the 10x Genomics’ scRNA-seq data ( Westoby et al, 2020 ), a good understanding of splicing changes can still be achieved due to the presence of a large number of junctional reads in the datasets and the application of a robust statistical approach ( Figure 1B ). Furthermore, due to the strong correlation between splicing changes and Braak NFT stages in AD ( Arizaca Maquera et al, 2023 ), the utilization of NFT and NGE single-cell data can provide a broader view of ASEs in PFC neuronal subtypes based on NFT pathogenesis and ASEs in different brain cell types based on Braak stages, respectively. A broad identification of ASEs can be gained by analyzing splicing alterations in various cell populations at different stages of AD progression.…”
Section: Introductionmentioning
confidence: 99%